CONSTRUCTING CULTURAL POLICIES IN ROMANIA. A POSSIBLE MODEL FOR COMMUNICATING THE NATIONAL VALUE SYSTEM - Ciocea, Mălina (POLISSEMA – Revista de Letras do ISCAP, 2019)
The premise of this paper is that a model for communicating the national value system must start from a strategy aimed at the identification, the cultivation and communication of values that give consistency to the value system. The analysis concentrates on the elements of such strategies and on the implications of applying a value communication program on the identity architecture of the community. The paper will also discuss the role of the national value system in the context of the emerging global culture, where the individual has the power to create his/her own hybrid cultural model.